Gramsci, Hegemony and Globalisation - Davidson, Alastair (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Antonio Gramsci’s point that battles are won and lost on the terrain of ideology is a much earlier and more complex explanation of the mediations between objective economic and social conditions and politics. It accounts generally for the fact that the continuation of contradiction—as must ever be the case under capitalism—and the worsening conditions for the majority of the world’s population do not mean the emergence of a political opposition to capitalism. Put simply, the great traditional workforces cannot strike at capitalism in its new heart. On the other hand, the two percent might be able to do so if it was not disaggregated because of its dispersal in new workforces that have no central workplaces or sufficient shared experience to overcome cultural differences, which divide rather than unite—if it did not live the new space-time relation. This labour mobility undoes class formation, even among those who do not share in the benefits of globalisation but dream of doing so. It remains to be seen whether the new nationalism and its closed borders, which keep such migrants at home with their contradictions, will foster conditions for the constitution of new collective working-class consciousness. Global capitalism fixes class relations in an impure state—a pure duality of capitalists and proletariat never develops anywhere. This means that any socialist transformation requires the building of a cross-class alliance of majorities on national-popular bases, rather than class. Therefore, that hegemony, which permits new ideas to become social forces, has to win out over the old hegemony in an organisational “war of position.”
Keywords: Antonio Gramsci; hegemony; globalisation